(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2015)
This section “History and Memory” offers to its readers an outstanding document entitled “Outcomes of the report draft by the members of the working group mandated to investigate on criminal infiltration and on the presence of organized crime groups in non-traditional areas”. This special working group was established during the XI legislature within the anti-mafia Parliamentary Commission held, at that time, by Luciano Violante. The group was coordinated by the Senator Carlo Smuraglia and they worked for two years (1992-1994). We publish the first part of the document dedicated to “The Phenomenon”. The entire report comprises two more parts: one dedicated to “The investigations of criminal offences” and the other one to “Suggestions and proposals”. The report was approved on 13th January 1994 and six days after it was sent to the President of the Chamber of Deputies, Giorgio Napolitano, and to the President of the Senate, Giovanni Spadolini.